Outcomes following pharyngeal reconstruction in total laryngectomy – Institutional experience and review of literature - Deepak Balasubramanian; Narayana Subramaniam; Priyank Rathod; Samskruthi Murthy; Mohit Sharma; Jimmy Mathew; Krishnakumar Thankappan; Subramania Iyer (Indian Journal of Plastic Surgery)
Background: Pharyngeal reconstruction is a challenging aspect of reconstruction after resections for head-and-neck cancer. The goals of reconstruction are to restore the continuity of the pharyngeal passage to enable oral alimentation and rehabilitation of speech wherever possible. This study was performed to determine the outcomes following pharyngeal reconstruction in total laryngectomy (TL) using different reconstructive options and to determine the predictors of pharyngocutaneous fistula (PCF) and swallowing dysfunction. Materials and Methods: Retrospective analysis of patient data between 2003 and 2010 of patients undergoing TL with partial or total pharyngectomy. Demographic and treatment details were collected and analysed. Univariate analysis was performed to determine predictors of PCF and swallowing dysfunction. Results: Fifty-seven patients underwent pharyngeal reconstruction following TL, 31 of whom had received prior treatment. Following tumour resection, 31 patients had circumferential defects and 26 patients had partial pharyngeal defects. The flaps used include pectoralis major myocutaneous flap (n = 29), anterolateral thigh flap (n = 8), gastric pull-up (n = 13) and free jejunal flap (n = 7). PCF was seen in 20 patients, of which 15 (75%) were managed conservatively and 5 required another surgery. At last follow-up, 99 patients (68%) were on full oral alimentation. Tracheo-oesophageal puncture and prosthesis insertion was done in 20 patients, of whom 17 (85%) developed satisfactory speech. Partial pharyngeal defects were associated with a higher risk of PCF on univariate analysis (P = 0.006) but were not significant on multivariate analysis. Post-operative swallowing dysfunction was significantly higher with hypopharyngeal involvement by tumour (P = 0.003). Conclusion: Pharyngeal reconstruction in TL is feasible with good results. Majority of the patients swallow and regain acceptable swallowing function within 3 months.